How does women’s empowerment relate to antenatal care attendance? A cross-sectional analysis among rural women in Bangladesh - Solis Winters; Helen O. Pitchik; Fahmida Akter; Farzana Yeasmin; Tania Jahir; Tarique Md. Nurul Huda; Mahbubur Rahman; Peter J. Winch; Stephen P. Luby; Lia C. H. Fernald (BMC Pregnancy and Childbirth, 2023)
Abstract Background In South Asia, roughly half of women attend at least four antenatal care visits with skilled health personnel, the minimum number recommended by the World Health Organization for optimal birth outcomes. A much greater proportion of women attend at least one antenatal care visit, suggesting that a key challenge is ensuring that women initiate antenatal care early in pregnancy and continue to attend after their first visit. One critical barrier to antenatal care attendance may be that women do not have sufficient power in their relationships, households, or communities to attend antenatal care when they want to. The main goals of this paper were to 1) understand the potential effects of intervening on direct measures of women’s empowerment—including household decision making, freedom of movement, and control over assets—on antenatal care attendance in a rural population of women in Bangladesh, and 2) examine whether differential associations exist across strata of socioeconomic status. Methods We analyzed data on 1609 mothers with children under 24 months old in rural Bangladesh and employed targeted maximum likelihood estimation with ensemble machine learning to estimate population average treatment effects. Results Greater women’s empowerment was associated with an increased number of antenatal care visits. Specifically, among women who attended at least one antenatal care visit, having high empowerment was associated with a greater probability of ≥ 4 antenatal care visits, both in comparison to low empowerment (15.2 pp, 95% CI: 6.0, 24.4) and medium empowerment (9.1 pp, 95% CI: 2.5, 15.7). The subscales of women’s empowerment driving the associations were women’s decision-making power and control over assets. We found that greater women’s empowerment is associated with more antenatal care visits regardless of socioeconomic status. Conclusions Empowerment-based interventions, particularly those targeting women’s involvement in household decisions and/or facilitating greater control over assets, may be a valuable strategy for increasing antenatal care attendance. Trial registration ClinicalTrials.gov Identifier: NCT04111016, Date First Registered: 01/10/2019.